Current understanding of the contribution of lactate to the cardiovascular system and its therapeutic relevance - Wu, Panyun; Zhu, Tengteng; Huang, Yiyuan; Fang, Zhenfei; Luo, Fei (Frontiers in Endocrinology, 2023)
Research during the past decades has yielded numerous insights into the presence and function of lactate in the body. Lactate is primarily produced via glycolysis and plays special roles in the regulation of tissues and organs, particularly in the cardiovascular system. In addition to being a net consumer of lactate, the heart is also the organ in the body with the greatest lactate consumption. Furthermore, lactate maintains cardiovascular homeostasis through energy supply and signal regulation under physiological conditions. Lactate also affects the occurrence, development, and prognosis of various cardiovascular diseases. We will highlight how lactate regulates the cardiovascular system under physiological and pathological conditions based on evidence from recent studies. We aim to provide a better understanding of the relationship between lactate and cardiovascular health and provide new ideas for preventing and treating cardiovascular diseases. Additionally, we will summarize current developments in treatments targeting lactate metabolism, transport, and signaling, including their role in cardiovascular diseases.